The training of the physician-teacher for the university educational practice, a hermeneutic look beyond schooling (Boletin Médico de Postgrado, 2024)
University teacher training should encourage the search for a new approach in teaching that emphasizes thinking while promoting epistemological links that contribute to a transdisciplinary conception that raises the idea of training based on the research process, rescuing the idea of the subject as an expression of sensitivity. For this reason, the purpose of this research was to generate a theoretical reflection on the training of the teaching physician for university educational practice. An in-depth interview was used as a strategy to obtain the key informants' version, applied to three medical social actors with teaching functions belonging to the Dean's Office of Health Sciences-UCLA. For its interpretation, it was systematized in order to codify and categorize it, through a categorical synthesis and triangulation. The credibility of the knowledge was cemented through the confidence in the interpretations made to the narrative of the social actors, through the systematic return or return to them, which accounted for the legitimacy to subsequently make the final reflections. This paradigm made it possible to study the phenomenon, as an act of consciousness based on experiences, in a scientific environment and to generate theoretical reflections for the evaluation of the training of doctors-teachers at UCLA/DCS.